Alterations in regional homogeneity of resting‐state brain activity in mesial temporal lobe epilepsy. (7th January 2013) - Zeng, Hongwu; Pizarro, Ricardo; Nair, Veena A.; La, Christian; Prabhakaran, Vivek
Summary Purpose The purpose of the present study was to identify abnormal areas of regional synchronization in patients with mesial temporal lobe epilepsy and hippocampus sclerosis (mTLE‐HS) compared to healthy controls, by applying a relatively novel method, the Regional Homogeneity (ReHo) method to resting state fMRI (RS‐fMRI) data. Methods Eyes closed RS‐fMRI data were acquired from 10 mTLE‐HS patients (four right‐side, six left‐side) and 15 age‐ and gender‐matched healthy subjects, and were analyzed by using ReHo. For group analysis, four right‐side MTLE‐HS patients' functional images were flipped, in order to make a homogeneous left MTLE‐HS group (10 cases) and increase the sample size. Key Findings Compared to the healthy control group, patients showed significantly increased ReHo in ipsilateral parahippocampal gyrus, midbrain, insula, corpus callosum, bilateral sensorimotor cortex, and frontoparietal subcortical structures, whereas decreased ReHo was observed mainly in default mode network (DMN) (including precuneus and posterior cingulate gyrus, bilateral inferior lateral parietal, and mesial prefrontal cortex) and cerebellum in patients relative to the control group. Significance This study identified that ReHo pattern in mTLE‐HS patients was altered compared to healthy controls. We consider decreased ReHo in DMN to be responsible for wide functional impairments in cognitive processes. We propose that the increased ReHo in specific regions may form a network that might be responsible for seizure genesis and propagation.